The Effect of Achievement Needs and Work Environment on Employee Performance: Study at a Construction Company in Bandung Regency - Rikeu Rahmawati; Ujang Wawan Sam Adinata (Jurnal Computech & Bisnis (e-journal), 2022)
Researchers conducted research intending to know the effect of Achievement Needs and Work Environment on Employee Performance at a Construction Company in Bandung Regency. Moreover, this research analyzes the factor that has the most dominant influence between the need for achievement and the work environment on employee performance at a construction company in Bandung Regency, which is the object of this study; as many as 41 respondents used a questionnaire. Based on research using path analysis, the variable need for achievement and work environment in one of the construction companies in Bandung Regency is valid. Therefore, the conclusions and considerations related to the research results pay attention to the need for achievement and the work environment to improve employee performance. The results showed that the Need for Achievement (X1) significantly influences Employee Performance (Y). Furthermore, the work environment (X2) significantly influences employee performance (Y). Companies where employees work, need to pay attention and create a work environment that makes employees feel at home and comfortable working. Companies can provide complete work facilities and tools to support employees at work. Companies need to pay attention to the lighting in the workspace so that employees can work optimally and minimize errors in work. A good work environment will encourage employees to be enthusiastic and feel at home at work. It can increase their sense of responsibility to do a better job towards improving employee performance. In increasing the Need for Achievement of employees at a construction company in Bandung Regency, the company should pay attention to the indicators that influence it. By providing motivation to its employees and monitoring the performance improvement of each employee more so that if the motivation and work environment of the employees is good, then good performance will also be created.